Professional Translators’ Theorising Patterns in Comparison with Classroom Discourse on Translation: The Case of Japanese/English Translators in the UK - Sakamoto, Akiko (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
If we aim to offer translation education that prepares our students adequately for their future professional career, it is important to recognise the different subcultures of translation, particularly those of professional translators and translation academics/teachers. The present study describes how the subculture of working translators theorise their practice, specifically, what concepts they use when they justify their translations. Seventeen Japanese/English translators, all commercially successful professionals who work in the UK, were interviewed about their experience of conflictive situations with their clients. In this article, I present an analysis of their justifications of their translation choices using a grounded theory approach. The analysis identifies the concept of the Role of Participants as the most prominent concept in the translators’ discourse. It also highlights several sub-concepts which relate to the main concept in intricate ways. These sub-concepts include Relationship, Knowledge of Language, Time and Effort, Authority and Natural/Literal Translation. The translators’ theorization is compared with classroom discourse about translation and the differences and similarities are discussed.